Engaging in educational research : revisiting policy and practice in Bangladesh - Chowdhury, Raqib; Sarkar, Mahbub; Mojumder, Foez; Roshid, M Moninoor (Education in the Asia-Pacific region: Issues, concerns and prospects,, 2018)
This book reflects the paradigm shift now manifesting in Bangladesh's education system by highlighting recent empirical research. It shares essential insights by presenting research conducted on diverse aspects of current day education in Bangladesh, including policy and governance, equity, access and participation, curriculum and pedagogy, assessment, and education programs and projects run by NGOs. Further, it offers a platform for these unique studies to be showcased and disseminated to scholars and researchers from developing and developed countries alike, and represents a unique reference resource for the education research community in Bangladesh, Asia and all over the world.